A multilivel analysis Investigating factors influencing individual readiness score (IRS) of soldiers in combat units - Pondanera, Jonathan L.
Abstract (This paper investigated the factors influencing the level of readiness of soldiers assigned in the combat units of the Philippine Army. Hierarchal Linear Modeling (HLM), frequently referred to as multilevel modeling was used in investigating the factors affecting the level of soldier's individual readiness score (IRS). Results revealed the soldier's rank and marital status significantly affect the soldier's level of readiness. Married soldiers tend to have more experience and senior-in-rank soldiers significantly affect the between platoon's variation in level of readiness. However, the study did not find empirical evidence on the soldier's experience and the number of their dependents significantly influence the level of readiness core. Similarly, the study did not find significant relationship on the influence of platoon sergeant experience and platoon leader appraisal score on the variations of readiness between platoons).
June 2018
Thesis (M.S. Statistics)--University of the Philippines, Diliman.
Keywords: Likelihood ratio test